Entrepreneurial Education, Green Orientation Entrepreneur, dan Green Value terhadap Ecology Entrepreneurial Intention - Edward Marchel Hugo; Kartika Nuringsih (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this research is to determine the impact of entrepreneurialeducation, green orientantion entrepreneur, and green value against the ecology entrepreneurial intention of Tarumanagara University students in West Jakarta. The samples used in this research were 100 respondents who were students of Tarumanagara University in West Jakarta. This research uses Smart Partial Least Square (PLS)software version 3.0 as a data analysis method. The results of this research indicates that green orientation entrepreneur and green value affects the ecology entrepreneurial intention, while the entrepreneurial education does not affect the ecology entrepreneurial intention. Penelitian ini bertujuan untuk mengetahui pengaruh entrepreneurial education, green orientantion entrepreneur,dan green value terhadap ecology entrepreneurial intention pada mahasiswa Universitas Tarumanagara Jakarta. Jumlah sampel yang digunakan dalam penelitian ini sebanyak 100 responden yang merupakan mahasiswa/I Universitas Tarumanagara di Jakarta. Penelitian ini menggunakan Software Smart Partial Least Square (PLS)versi 3.0 sebagai metode analisis data. Hasil penelitian menunjukkan bahwa green orientantion entrepreneurdan green value berpengaruh terhadap ecology entrepreneurial intention, sedangkan entrepreneurial education tidak memiliki pengaruh terhadapecology entrepreneurial intention.